An efficient Ni–P amorphous alloy electrocatalyst with a hierarchical structure toward borohydride oxidation. Issue 29 (7th July 2021) - Yu, Jingjing; Hu, Bihao; Xu, Chuanlan; Meng, Jiazhi; Yang, Shu; Li, Yan; Zhou, Xiaoyuan; Liu, Yuping; Yu, Danmei; Chen, Changguo
Abstract : A Ni–P@NF amorphous alloy catalyst electrode with a unique hierarchical structure shows excellent catalytic activity, stability and durability toward borohydride oxidation. Abstract : Nickel has been widely researched in the electrooxidation of borohydride due to its low cost and abundant reserves, but its catalytic activity and stability need to be improved for practical application. In this work, a Ni and P deposited nickel foam (Ni–P@NF) catalyst electrode with a unique hierarchical structure is prepared by a simple one-step electrodeposition method. The structure, morphology, and catalytic performances of Ni–P@NF are investigated systematically. The results show that Ni–P@NF exhibits excellent catalytic activity, stability, and durability during borohydride electrooxidation. On the Ni–P@NF catalyst electrode, the current density for borohydride oxidation can reach 225 mA cm −2 ; the fuel utilization is up to 84% and 97% of the initial current is maintained even after 500 cycles of cyclic voltammetry (CV), while a traditional H-type direct sodium borohydride fuel cell (DBFC) assembled with a Ni–P@NF catalyst anode can deliver a maximum power density of 52.5 mW cm −2 and an open circuit potential of 1.87 V. These merits can be attributed to the unique hierarchical structure of the Ni–P catalyst and the introduction of phosphorus. The results also show that the Ni–P@NF catalyst has certain application potential in DBFCs.